Biodiesel exhaust–induced cytotoxicity and proinflammatory mediator production in human airway epithelial cells. Issue 1 (5th July 2014) - Mullins, Benjamin J.; Kicic, Anthony; Ling, Kak‐Ming; Mead‐Hunter, Ryan; Larcombe, Alexander N.
ABSTRACT: Increasing use of biodiesel has prompted research into the potential health effects of biodiesel exhaust exposure. Few studies directly compare the health consequences of mineral diesel, biodiesel, or blend exhaust exposures. Here, we exposed human epithelial cell cultures to diluted exhaust generated by the combustion of Australian ultralow‐sulfur‐diesel (ULSD), unprocessed canola oil, 100% canola biodiesel (B100), and a blend of 20% canola biodiesel mixed with 80% ULSD. The physicochemical characteristics of the exhaust were assessed and we compared cellular viability, apoptosis, and levels of interleukin (IL)‐6, IL‐8, and Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) in exposed cultured cells. Different fuel types produced significantly different amounts of exhaust gases and different particle characteristics. All exposures resulted in significant apoptosis and loss of viability when compared with control, with an increasing proportion of biodiesel being correlated with a decrease in viability. In most cases, exposure to exhaust resulted in an increase in mediator production, with the greatest increases most often in response to B100. Exposure to pure canola oil (PCO) exhaust did not increase mediator production, but resulted in a significant decrease in IL‐8 and RANTES in some cases. Our results show that canola biodiesel exhaust exposure elicits inflammation and reduces viability of human epithelial cell cultures in vitro when compared with ULSD exhaust exposure. This may be related to an increase in particle surface area and number in B100 exhaust when compared with ULSD exhaust. Exposure to PCO exhaust elicited the greatest loss of cellular viability, but virtually no inflammatory response, likely due to an overall increase in average particle size. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 44–57, 2016.